2012
DOI: 10.1111/j.1464-410x.2012.11241.x
|View full text |Cite
|
Sign up to set email alerts
|

Can simvastatin improve erectile function and health‐related quality of life in men aged ≥40 years with erectile dysfunction? Results of the Erectile Dysfunction and Statins Trial [ISRCTN66772971]

Abstract: What's known on the subject? and What does the study add?• Erectile dysfunction (ED) is often associated with endothelial dysfunction. It is also recognized as a marker for underlying vascular disease. There are missed opportunities to address cardiovascular risk factors in these men.• Simvastatin administered for 6 months improves sexual health-related quality of life in men aged Ն40 years with untreated ED. It reduces the risk of future cardiovascular events via a reduction in serum cholesterol in men with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…In a prospective observational study among 93 men it was suggested that ED following statin therapy is more likely in patients with severe endothelial dysfunction due to established cardiovascular risk factors, including age, smoking and diabetes [69]. On the other hand, statins have been reported to improve erectile function when the cohorts had no other cardiovascular risk factors accept for untreated ED [7072]. Furthermore, statins seem to increase the beneficial effects of sildenafil through endothelial function benefits [7376].…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective observational study among 93 men it was suggested that ED following statin therapy is more likely in patients with severe endothelial dysfunction due to established cardiovascular risk factors, including age, smoking and diabetes [69]. On the other hand, statins have been reported to improve erectile function when the cohorts had no other cardiovascular risk factors accept for untreated ED [7072]. Furthermore, statins seem to increase the beneficial effects of sildenafil through endothelial function benefits [7376].…”
Section: Resultsmentioning
confidence: 99%
“…In our previously published trial [6], there was a nonsignificant change in erectile function due to simvastatin treatment, although patients with more severe ED at baseline showed a larger improvement than patients with mild/moderate ED. However, simvastatin significantly improved the male ED-specific quality of life (MED-QoL), LDL cholesterol and reduced future cardiovascular risk [6].…”
Section: Introductionmentioning
confidence: 98%
“…Although ED affects sexual and mental health [1,2], the rates of consultation for ED remain low [3,4] and not all patients respond to Sildenafil and other phosphodiesterase inhibitors [5]. We reported the results of a randomised controlled trial (RCT) evaluating the effectiveness and cost effectiveness of simvastatin therapy in men with ED in men with untreated ED, but without significant cardiovascular risk factors [6]. The lipid lowering drug simvastatin was chosen for this study because ED shares risk factors with cardiovascular disease (CVD) [7-11].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with high cardiovascular risk, hypertension, and angina and those already on ED or statin therapy were excluded. No signifi cant difference in erectile function between the simvastatin and placebo groups ( p = 0.27) was noted [ 31 ].…”
Section: Clinical Studiesmentioning
confidence: 98%